Spatial regional electricity intensity and equitable well-being to support just transition - Balletto, Ginevra; Sinatra, Martina; Milesi, Alessandra; Ghiani, Emilio; Borruso, Giuseppe; Zullo, Francesco (TeMA - Journal of Land Use, Mobility and Environment, 2023)
The European Union has set ambitious targets for energy efficiency to promote energy sustainability and decarbonisation of energy systems by introducing performance indicators that can be used in different contexts at international, national or regional level. In particular, the macroeconomic indicator of Electrical Intensity (EI) and Sustainable Electrical Intensity (SEI) can be used to measure energy performance on different scales, to identify the amount of energy used per unit of Gross Domestic Product (GDP), thus providing a picture of sustainability in economic and spatial terms. In order to support appropriate urban and territorial policies that can have a positive effect not only on GDP, but more generally on the fair and sustainable well-being of citizens, the complexity of the EI must be addressed by assessing the impacts of energy efficiency interventions and the development of renewable energy installations. The aim of the work is to develop a comparative approach between the spatial distribution the total electricity consumption (EI index) and the total renewable electrical consumption (SEI index) of the Italian Regions - and a dataset of BES indicators - Equitable and Sustainable Well-being - to evaluate of the regional electricity transition.